2000
DOI: 10.4049/jimmunol.164.9.4433
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of T Cell Activation Using a Surface-Linked Single-Chain Antibody to CTLA-4 (CD152)

Abstract: CTLA-4 (CD152) engagement can down-regulate T cell activation and promote the induction of immune tolerance. However, the strategy of attenuating T cell activation by engaging CTLA-4 has been limited by sharing of its natural ligands with the costimulatory protein CD28. In the present study, a CTLA-4-specific single-chain Ab (scFv) was developed and expressed on the cell surface to promote selective engagement of this regulatory molecule. Transfectants expressing anti-CTLA-4 scFv at their surface bound soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 72 publications
4
54
0
Order By: Relevance
“…CTLA-4 ligation on previously activated T cell blasts has been shown to rapidly inhibit the phosphorylation of the CD3 chain and the Src kinase ZAP-70 (28,29). A similar study demonstrated that ligation of CTLA-4 regulates the phosphorylation and activation of the downstream-signaling molecules ERK and JNK (30).…”
Section: Discussionmentioning
confidence: 50%
“…CTLA-4 ligation on previously activated T cell blasts has been shown to rapidly inhibit the phosphorylation of the CD3 chain and the Src kinase ZAP-70 (28,29). A similar study demonstrated that ligation of CTLA-4 regulates the phosphorylation and activation of the downstream-signaling molecules ERK and JNK (30).…”
Section: Discussionmentioning
confidence: 50%
“…The rationale behind anti-CTLA-4 Ab therapy is that it enhances immune responses against tumor Ags primarily by enhancing tumor-specific effector T-cell responses. With regard to boosting effector T-cell responses, however, blockade of CTLA-4 is surprisingly inconsistent; with several groups reporting that blockade of mCTLA-4 interaction with B7 ligands in the presence of TCR coactivation can actually inhibit T-cell activation [39][40][41][42][43][44]. In particular, experiments in which cell surface cross-linking of mCTLA-4 occurs demonstrate the capacity of anti-CTLA-4 antibodies to inhibit T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which CTLA-4 may induce T cell inhibition involves recruitment of the Src homology-2 domain-containing protein tyrosine phosphatase-1 (12) and protein phosphatase 2A (13,14) to the vicinity of the T cell receptor (TCR) in the immune synapse (15,16). This recruitment may result in dephosphorylation of the signaling molecules within the TCR complex (17) and consequent termination of T cell activation.…”
mentioning
confidence: 99%
“…These ligands must be provided in the cis configuration and expressed on the same APC that activates the T cell (17). Hence, effective CTLA-4-mediated inhibition of T cells requires both proper configuration of the effector molecules and correct timing of their interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation